The Short Form of the Revised Almost Perfect Scale - Rice, Kenneth G.; Richardson, Clarissa M. E.; Tueller, Stephen (Journal of personality assessment, 2014)
We created a shorter and more refined item set from the Almost Perfect Scale-Revised (APS-R; Slaney, Mobley, Trippi, Ashby, & Johnson, 1996; Slaney, Rice, Mobley, Trippi, & Ashby, 2001) to measure 2 major dimensions of perfectionism: standards (high performance expectations) and discrepancy (self-critical performance evaluations). In Study 1, after testing the internal structure of the measure (N = 749), a subset of the current APS-R items was derived (Short Almost Perfect Scale [SAPS]) that possessed good psychometric features, such as strong item-factor loadings, score reliability, measurement invariance between women and men, and criterion-related validity through associations with neuroticism, conscientiousness, academic performance, and depression. Controlling for neuroticism and conscientiousness, factor mixture modeling supported a 2-factor, 3-class model of perfectionism, and results were consistent with labeling the classes as nonperfectionists and adaptive and maladaptive perfectionists. Measurement results were cross-validated in a separate sample (N = 335). Study 2 also provided substantial evidence for the convergent, discriminant, and criterion-related validity of SAPS scores. Both studies supported the SAPS as a brief and psychometrically strong measure of major perfectionism factors and classes of perfectionists.